Pemberdayaan Masyarakat Industri Kreatif Peduli Lingkungan Studi kasus Kelompok Pengrajin Daur Ulang Plastik di Kelurahan Jambangan, Surabaya - sri juni woro astuti (UII, 2018)
The phenomenon of waste becomes an urban issue that is difficult to overcome, especially plastic waste that decomposition process takes a very long time. But actually plastic waste is a waste that can be recycled into useful items so as to reduce the environmental impact significantly. In Surabaya there are community care environment groups that recycle plastic waste to be processed into a variety of creative products and have economic value. However, their activities are still experiencing difficulties such as limited equipment, and motivation of members that still need to be improved. Through this empowerment activities is expected to provide solutions to the problems faced by the group of recycling plastic waste craftsmen in the Village Jambangan Surabaya and at the same time provide solutions to environmental pollution due to increasing plastic waste. The approaches offered to solve the partner problems are participatory and interactive approaches to address issues of dialogue, discussion to gain agreement with partners. The results obtained after the existence of this program can be seen the increase in the number of production and there is also additional diversification of products so that their income also increased.